Morbid Adherent Placenta among Pregnant Women prior to Cesarean Delivery: Experience of 15 Cases at a Tertiary care Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Morbid adherent placenta among pregnant women is a very serious condition.Objective: The purpose of the present study was to identify the risk factors predisposing to morbidly adherent placenta, different modes of management and maternal and neonatal outcomes.Methodology: This cohort study was conducted in the Department of Obstetrics and Gynaecology in Enam Medical College, Dhaka, Bangladesh from January to December 2018 for a period of one (01) year. The study included all pregnant women, irrespective of parity status, with gestational age more than 29 weeks who had any type of morbid adherent placenta. The diagnosis was made only during attempted manual removal when the plane of cleavage between the placenta and the uterine wall could not be made out. The complete history, physical examination of the patient along with relevant investigations for diagnosis of morbid adherent placenta were documented. The mood of the presentation of the patient and duration of gestation, history of previous lower segment or classical caesarean section or other intrauterine operative procedure, by lateral uterine ligation, internal iliac artery ligation, hysterectomy-classical or lower segment or peri-partum, neonatal outcome and duration of the hospital stay all were recorded.Result: The incidence of morbidly adherent placenta was 12.75 per 1000 pregnancies. Patient profile comprising third gravida in the age group of 25 to 28 years, 92 % of the patient in this study have previous caesarean section and co-existing placenta praevia was diagnosed in 93%. 47% of the women delivered between 36 & 38 weeks. Caesarean section was the mode of delivery in 93% of the patient.Conclusion: In conclusion young adult women with previous caesarean section with co-existenting of placenta praevia are the most commonly suffering from morbidly adherent placentaJournal of National Institute of Neurosciences Bangladesh, 2020;6(1): 33-37